G331(P) Developing parental pathways: The most effective way to care for children with constipation – a cumbrian experience. (27th April 2016) - Shabde, N; Harrison, H
Abstract : Aims: Share the Cumbrian experience of the development of a child centred constipation pathway, based on NICE guidance which has been used to empower and support families and professionals to ensure best outcomes for children in a community setting. Methods: The main objective of the project was to engage families and professionals to steam-line the service for Children with constipation and to ensure that the service was responsive, consistent, CYP centred, evidence based with a strong Public Health education focus. Although a common condition in childhood there was a concern that constipation was being managed ineffectively with poorer outcomes probably due to: inconsistent diagnostic practice inconsistent prescribing high levels of hospital attendance significant levels of consultant follow up lack of liaison with community services A multi-disciplinary group was established in 2009 to identify the way forward. The group consisted of commissioners, health visitors, school nurses, public health, GPs, parents/carers and acute paediatricians. A total of two workshops were undertaken to develop the pathway with a number of engagement sessions with parents/carers based at children's centres throughout Cumbria. This informed a clear need to develop a model based on the Cumbrian consensus to improve the quality of service with better outcomes. Results: Implementation of the pathway saw a demonstrable reduction in the numbers of admissions into hospital for children and young people. Over a period of 3 years (2010–2013) referrals were almost halved. This demonstrates that the use of a family friendly, informative and colourful leaflet can have a direct effect on health related issues (Tables 1 and 2). Current data suggests that there is a slight increase in hospital admissions. This can be due to a number of factors including a change of personnel, increase reliance on locum staff, increased pressure of work. Conclusion: The pathway speaks directly to children, young people and their parents, making it clear 'their entitlement' from NHS services. The pathway makes clear what children, young people, and their families should expect and can hold professionals to account (Figure 1 ).